Research handbook on Chinese environmental law edited by Qin Tianbao. - Qin, Tianbao, 1975- (Research handbooks in environmental law., 2015)
This authoritative Research Handbook presents, for the first time, a comprehensive overview of the salient content and major developments in environmental law in transitional China. Through this rigorous examination, it gives a unique insight into the implementation problems and reform needs of environmental governance in China. This timely book explores the core concepts, basic mechanisms and key challenges of Chinese environmental law, extending the frontier of understanding in this fundamental area. Combining theory and practice, the expert contributors provide an introduction to and comments on relevant environmental laws and regulations and their latest developments. The Research Handbook builds upon previous knowledge of Chinese environmental law, divulging concerns on redressing environmental protection issues in the context of economic growth and sustainable development. Readers will gain a discerning insight into the nuances of environmental regulation in China from this extensive review. This necessary exploration of Chinese environmental law will be an indispensible reference point for academics and advanced students of environmental studies in general, and environmental law in particular. Practitioners will find the work both informative and important.